MODELLING TRAFFIC NOISE LEVEL ON ROADSIDE TRADERS AT WURUKUM MARKET AREA IN MAKURDI TOWN, BENUE STATE – NIGERIA (Nigerian Journal of Technology, 2017)
Noise level prediction model was built for road side traders at an open market area of Wurukum market in Makurdi town. One week survey was carried out to measure noise level, traffic volume, vehicles speeds and distances from the edge of road shoulder. The study revealed that roadside traders expose themselves to average noise levels of 82.33dB (A), 77.48dB (A) and 74.38dB (A) at distances of 0m, 5m and 10m respectively from the edge of roadway. At 0m, the noise level was slightly below World Health Organization (WHO) specification of 85dB (A), beyond which noise pollution is hazardous. At 10m, the noise level was above minimum safe level of 55dB (A). The model indicates high level of ambient noise which was attributed to intensive market activities from the background. The model was checked using Chi square test at 5% level of significance and coefficient of determination (R2=0.7216) which gave satisfactory results. A strategy of relocation and splitting the market was proposed for local government council’s consideration.  http://dx.doi.org/10.4314/njt.v37i1.4